Determination of Trimebutine and Desmethyl-trimebutine in Human Plasma by HPLC - Lavit, Michel; Saivin, Sylvie; Boudra, Hamid; Michel, Frank; Martin, Arnaud; Cahiez, Gérard; Labaune, Jean Pierre; Chomard, Jean Marie; Houin, Georges (Arzneimittelforschung, 2000)
A simple and sensitive HPLC method has been developed to measure trimebutine (CAS 39133-31-8, maleate: CAS 34140-59-5) and its main metabolite desmethyl-trimebutine in human plasma. The method was validated according to the Washington Consensus Conference on the Validation of Analytical Methods. It involved extraction of the plasma with n-hexane containing 2-pentanol, followed by reversed-phase HPLC using a Partisil® ODS2 10 μm column and UV detection at 265 nm. The retention times of the internal standard (procaine), desmethyl-trimebutine and trimebutine were 2.4, 4.3 and 6.5 min, respectively. The standard curves were linear from 20 ng · ml−1 (limit of quantitation) to 5000 ng · ml−1 for both compounds. The coefficient of variation for all the criteria of validation were less than 15%. The extraction recoveries obtained for trimebutine and desmethyl-trimebutine were about 90%. Both compounds were very stable upon storage in plasma. The method was tested by measuring the plasma concentrations following oral administration to humans during a bioequivalence study and was shown suitable for pharmacokinetic studies.
Keywords: CAS 34140-59-5; CAS 39133-31-8; Desmethyl-trimebutine, determination in plasma, HPLC; Trimebutine, determination in plasma, HPLC